PERMAINAN BAHASA UNTUK STIMULASI KEMAMPUAN BAHASA RESEPTIF ANAK USIA DINI - Desy Dela Tika (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2021)
Language games for stimulation early childhood receptive language. Receptive language is ability for listen and read. Receptive language development for children needs to be developed so that children can absorb information properly. For this reason, stimulation is needed so that the children’s receptive language can develop. One that can be do is playing language games. Language games can be done because basically playing is the main need for children. This research uses a literature study method where the data retrieval system in this research comes from books or journals that are analyzed based on existing problems. Language games that can be done to stimulate children's receptive language skills include repeating words, listening to them, guessing, whispering in chains and telling stories with indirect props. Stimulation with this method will make it easier for early childhood to develop their receptive language skills.